Momordica charantia, a Nutraceutical Approach for Inflammatory Related Diseases - Bortolotti, Massimo; Mercatelli, Daniele; Polito, Letizia (Frontiers in Pharmacology, 2019)
Momordica charantia, commonly called bitter melon, is a plant belonging to Cucurbitaceae family known for centuries for its pharmacological activities and nutritional properties. Due to the presence of many bioactive compounds, some of which possess potent biological actions, this plant is used in folk medicine all over the world for the treatment of different pathologies, mainly diabetes, but also cancer and other inflammation-associated diseases. It is widely demonstrated that Momordica charantia extracts contribute in lowering glycaemia in patients affected by type 2 diabetes. However, the majority of existing studies on Momordica charantia bioactive compounds were performed only on cell lines and in animal models. Therefore, because the real impact of bitter melon on human health has not been thoroughly demonstrated, systematic clinical studies are needed to establish its efficacy and safety in patients. Besides, both in vitro and in vivo studies have demonstrated that bitter melon may also elicit toxic or adverse effects under different conditions. The aim of this review is to provide an overview of anti-inflammatory and anti-neoplastic properties of bitter melon, discussing its pharmacological activity as well as the potential adverse effects. Even if a lot of literature is available about bitter melon as antidiabetic drug, few papers afford the anti-inflammatory and anti-cancer properties of this plant.